PENGARUH MODAL TENAGA KERJA DAN LAMA USAHA TERHADAP USAHA PENGEPUL SAMPAH ANORGANIK DI KOTA DENPASAR - Darmayana, Komang Jodi Arta; Kartika, I Nengah (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 7 (2020): VOL 9 NO 7, JULI 2020 (1431-1630), 2020)
The income of inorganic collectors in Denpasar during 2014-2018 experienced a decline. The purpose of this study was to analyze the effect of capital, labor and business length on inorganic waste collectors in Denpasar City. The number of samples taken was 54 inorganic waste collection businesses in Denpasar City, using the Proportional Random Sampling technique. Data collection is done through non-behavioral observation, structured interviews and in-depth interviews. The analysis technique used is multiple linear regression. Based on the analysis it was found that capital, labor and business length simultaneously had a significant effect on the inorganic collectors collectors' revenue in Denpasar City. Capital, labor and business duration partially have a positive and significant effect on the income of inorganic waste collectors in Denpasar City. The garbage collectors in Denpasar are advised to be able to maximize the use of capital, labor and business length in order to increase business income. Keywords: Capital, Labor, business length and income